Алгебра операторов Бергмана с автоморфными коэффициентами и параболической группой сдвигов - Мозель, В.А.; Чернецкий, В.А. (Український математичний журнал, 2001)
Вивчається алгебра операторів з ядром Бергмана, розширена ізометричними операторами зваженого зсуву. Коефіцієнти алгебри вважаються автоморфними відносно циклічної параболічної групи дробно-лінійних перетворень одиничного круга і неперервними на рімановій поверхні групи. За допомогою ізометричного перетворення одержано квазіавтоморфний матричний оператор на рімановій поверхні із властивостями, аналогічними властивостям оператора Бергмана. Це дає можливість побудувати алгебру символів, дати ефективний критерій фредгольмовості та обчислити індекс операторів розглянутої алгебри. We study the algebra of operators with the Bergman kernel extended by isometric weighted shift operators. The coefficients of the algebra are assumed to be automorphic with respect to a cyclic parabolic group of fractional-linear transformations of a unit disk and continuous on the Riemann surface of the group. By using an isometric transformation, we obtain a quasiautomorphic matrix operator on the Riemann surface with properties similar to the properties of the Bergman operator. This enables us to construct the algebra of symbols, devise an efficient criterion for the Fredholm property, and calculate the index of the operators of the algebra considered.